2002
DOI: 10.1111/j.1945-5100.2002.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Source and maintenance of the argon atmospheres of Mercury and the Moon

Abstract: Abstract-We propose that argon-40 measured in the lunar atmosphere and that in Mercury's atmosphere is due to current diffusion into connected pore space within the crust. Higher temperatures at Mercury, along with more rapid loss from the atmosphere, will lead to a similar or smaller column abundance of argon at Mercury than at the Moon, given the same crustal abundance of potassium. Because the noble gas abundance in the mercurian atmosphere represents current effusion, it is a direct measure of the crustal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The deep source origin for argon was first questioned by Hodges (1981) and, 25 years later, by Killen (2002). Applying a sophisticated multipath diffusion code, Killen (2002) showed that diffusion from the crust (i.e., a source much closer to the surface, $25 km) could account for the effusive flux of argon into the lunar atmosphere.…”
Section: Origin Of Argonmentioning
confidence: 98%
“…The deep source origin for argon was first questioned by Hodges (1981) and, 25 years later, by Killen (2002). Applying a sophisticated multipath diffusion code, Killen (2002) showed that diffusion from the crust (i.e., a source much closer to the surface, $25 km) could account for the effusive flux of argon into the lunar atmosphere.…”
Section: Origin Of Argonmentioning
confidence: 98%
“…Therefore the vapor ejected from impact vaporization will be the most representative of the surface composition. Potter and Morgan (1997) c Hodges (1974): model abundance d Morgan and Killen (1997): model abundances e Morgan and Killen (1997): model abundances f Sprague et al (1993): measured upper limit g Sprague et al (1996Sprague et al ( , 1995: prediction h Shemansky (1988): Mariner 10 measurements i Killen et al (1990): measured abundance j Bida et al (2000) k Killen (2002): model abundance l Killen and Ip (1999) m Huebner et al (1992) ionisation rates: experimental (e); theoretical (t) for quiet and active Sun n Sprague et al (1996) In addition, macro-meteors impact Mercury but at an unknown rate. provided the distribution of impact probability as a function of impactor radius, up to objects of 100 m in radius.…”
Section: Impact Vaporizationmentioning
confidence: 99%
“…However, the loss of ions by entrainment in the solar wind is not complete, even at the moon which is devoid of a magnetosphere. For example, Manka and Michel (1971) showed that 50% of the 40 Ar photoions, created by photoionization of the tenuous argon atmosphere, reimpact the surface of the moon, explaining the enhancement of argon in the lunar regolith (Killen 2002). At Mercury, loss of neutrals by Jeans escape and loss of photoions are both less efficient than at the moon due to Mercury's greater mass and its magnetosphere.…”
Section: Discussionmentioning
confidence: 99%